KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SMP - Muhammad Suharta; Sugiatno Sugiatno; Dede Suratman (Universitas Tanjungpura, 2020)
AbstractThis research aims to determine the students' critical thinking skills in learning mathematics using the CTL approach in SMP Negeri 5 Pontianak. The method used in this research was descriptive. This research was conducted for approximately two months from the pre-test to the post-test. Learning was carried out by the researcher himself. After the treatment was finished, the researcher gave a posttest to measure students' critical thinking skills in mathematics. It also provided a questionnaire for students to know their opinions on the learning conducted and conduct interviews with teachers. The results showed that students can do critical thinking processes in mathematics learning using a CTL approach in SMP Negeri 5 Pontianak. The students ability to think critically before being given learning with the CTL approach was relatively weak, with an average percentage of students on pre-test scores, which was 46% (good enough). The learning process took place systematically and students follow it carefully. The ability to think critically after learning with the CTL approach was in the good category, namely with an average percentage value of 75%. Learning with the CTL approach was considered to be able to improve students' critical thinking skills. This was based on the value of the effect size, which was equal to 0.5877 so that it can be said there is a large influence on learning with the CTL approach to critical thinking skills of students.Keywords : Contextual Teaching and Learning, Critical Thinking Skills, Learning Mathematics, SMP Negeri 5 Pontianak.